The D Domain of LRRC4 anchors ERK1/2 in the cytoplasm and competitively inhibits MEK/ERK activation in glioma cells. Issue 1 (December 2016) - Wang, Zeyou; Guo, Qin; Wang, Rong; Xu, Gang; Li, Peiyao; Sun, Yingnan; She, Xiaoling; Liu, Qiang; Chen, Qiong; Yu, Zhibin; Liu, Changhong; Xiong, Jing; et al.
Abstract Background As a well-characterized key player in various signal transduction networks, extracellular-signal-regulated kinase (ERK1/2) has been widely implicated in the development of many malignancies. We previously found that Leucine-rich repeat containing 4 (LRRC4) was a tumor suppressor and a negative regulator of the ERK/MAPK pathway in glioma tumorigenesis. However, the precise molecular role of LRRC4 in ERK signal transmission is unclear. Methods The interaction between LRRC4 and ERK1/2 was assessed by co-immunoprecipitation and GST pull-down assays in vivo and in vitro. We also investigated the interaction of LRRC4 and ERK1/2 and the role of the D domain in ERK activation in glioma cells. Results Here, we showed that LRRC4 and ERK1/2 interact via the D domain and CD domain, respectively. Following EGF stimuli, the D domain of LRRC4 anchors ERK1/2 in the cytoplasm and abrogates ERK1/2 activation and nuclear translocation. In glioblastoma cells, ectopic LRRC4 expression competitively inhibited the interaction of endogenous mitogen-activated protein kinase (MEK) and ERK1/2. Mutation of the D domain decreased the LRRC4-mediated inhibition of MAPK signaling and its anti-proliferation and anti-invasion roles. Conclusions Our results demonstrated that the D domain of LRRC4 anchors ERK1/2 in the cytoplasm and competitively inhibits MEK/ERK activation in glioma cells. These findings identify a new mechanism underlying glioblastoma progression and suggest a novel therapeutic strategy by restoring the activity of LRRC4 to decrease MAPK cascade activation.